Polyurethane cationomers synthesized from 4,4’-methylenebis(phenyl isocyanate), polyoxypropylene glycol and N-alkyldiethanoloamines - chemical structures and free surface energies and its components - Król, P.; Król, B. (Polimery, 2022)
Polyurethane cationomers were synthesized in the reaction of 4,4’-methylenebis(phenyl isocyanate), oligo(oxypropylene)diol and tertiary aliphatic or aromatic amines which, after the incorporation into the prepolymer in the reaction with formic acid, were converted into alkylammonium cations (Table 1). By chain extension of these products with 1,6-hexamethyleneamine, the stable aqueous dispersions were obtained forming thin polymeric films on the surface of polytetrafluoroethylene. The chemical structures of cationomers synthesized were confirmed with 1H NMR (Fig. 2-6, Table 3) and IR spectroscopy (Fig. 7 and 8). Some trials were made to characterize quantitatively the polarity of these structures’ fragments (Table 4 and 5). Free surface energy (SEP, γS) of ionomers obtained has been determined using the physical van Oss-Good’s model and contact angle measurements of PUR cationomers surfaces with model fluids showing different polarity (water, formamide or diiodomethane - Table 2). The effects of chemical structures (special attention has been paid to the hydrocarbon substituent at nitrogen atom of tertiary amine) and polarity of PUR cationomers on the values of SEP and its components: dispersive and acid-base ones were interpreted (Table 6). The structures of polyol and urethane segments of a cationomer and the kind of ionogenic segments were found as having the fundamental influences. The biggest SEP value was found for cationomer synthesized with N-methylphenyldiethanoloamine while the smallest one for cationomer obtained with N-t-butyldiethanoloamine.